2020
DOI: 10.1007/s10549-020-05644-z
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for prioritization, treatment, and triage of breast cancer patients during the COVID-19 pandemic. the COVID-19 pandemic breast cancer consortium

Abstract: The COVID-19 pandemic presents clinicians a unique set of challenges in managing breast cancer (BC) patients. As hospital resources and staff become more limited during the COVID-19 pandemic, it becomes critically important to define which BC patients require more urgent care and which patients can wait for treatment until the pandemic is over. In this Special Communication, we use expert opinion of representatives from multiple cancer care organizations to categorize BC patients into priority levels (A, B, C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
409
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 321 publications
(431 citation statements)
references
References 52 publications
3
409
0
6
Order By: Relevance
“…Cancer patients are at an increased risk of contagion, infection, morbidity and death [9][10][11]. Emergency guidelines for breast cancer treatment [13][14][15]32,33] have suggested postponing surgery when the risk of progression is low (luminal tumors), initiating NET, extending the application of NACT and/or target therapies to subtypes of adverse biology (TN and HER2), minimizing the extent of surgery, including avoiding the use of autologous tissue in breast reconstruction, and postponing prophylactic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Cancer patients are at an increased risk of contagion, infection, morbidity and death [9][10][11]. Emergency guidelines for breast cancer treatment [13][14][15]32,33] have suggested postponing surgery when the risk of progression is low (luminal tumors), initiating NET, extending the application of NACT and/or target therapies to subtypes of adverse biology (TN and HER2), minimizing the extent of surgery, including avoiding the use of autologous tissue in breast reconstruction, and postponing prophylactic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic and the emergency recommendations for EBC treatment impacted on the management strategies of Brazilian breast specialists. According to these recommendations [13][14][15]24,32,33], HRpositive EBC should preferentially be treated using NET. Some societies have suggested that recommendations for the treatment of EBC should be classi ed by degree of priority according to the advice provided in the Ontario Health Pandemic Planning Clinical Guideline for Patients with Cancer [37], with cases of luminal tumors being classi ed as Priority B and surgery being postponed for 3-6 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations